Translation, cross-cultural adaptation and validation of the Chinese version of the IBD-Control questionnaire: A patient-reported outcome measure in inflammatory bowel disease. - Bingmei Guo; Haihong Li; Qing Cui; Jie Li; Yanbo Yu; Zhen Li; Junwen Wang (PLoS ONE)
Background A demand exists for user-friendly patient-reported outcome measures for patients with inflammatory bowel disease (IBD). The IBD-Control Questionnaire has been recently developed to assess overall disease control from the patient's view but has not been available in China. Methods Translation and cultural adaption of the IBD-Control into Chinese was conducted through four steps (forward translation, backward translation, expert panel, and pilot testing). Afterwards, a prospective validation study was conducted from February 2022 to February 2023. The translated IBD-Control, Short Health Scale, EQ-5D-5L, and disease activity measurements using either the Physician Global Assessment and Simple Clinical Colitis Activity Index or the Crohn's Disease Activity Index were used. Acceptability, test-retest reliability, internal consistency, content validity, convergent validity, structural validity, discriminant ability, and receiver operating characteristic curves were analyzed. Results Questionnaires were completed by 150 participants with IBD (31 with Crohn's disease [CD] and 119 with ulcerative colitis [UC]). The Cronbach's alpha coefficient was 0.823 for the IBD-Control-8 scale. The correlations between individual item and total score varied from 0.485 to 0.892 among CD patients and from 0.588 to 0.712 among UC patients. The S-CVI/Ave was 0.98. Convergent validity analyses exhibited moderate to strong correlations between other measurements and IBD-Control-8-subscore (0.555-0.675) or IBD-Control VAS (0.503-0.671). Test-retest analysis showed that the mean scores were 75.23±17.33 versus 72.10±14.99 (r = 0.894, p<0.01) for VAS scores and 12.75±3.49versus 12.80±3.29 for IBD-Control-8 subscore (r = 0.963, p<0.01), respectively. The IBD-Control-8-subscore and IBD-Control-VAS exhibited significant discriminative capability among the PGA categories (ANOVA, p < .001). The ROC analysis revealed an optimal cut-off point for the IBD-Control-8 subscore of 14 points (sensitivity: 70.9%, specificity 83.5%), versus a cut-off of 70 on the IBD-Control VAS score (sensitivity: 84.4%, specificity 69.3%). Conclusion The Chinese IBD-Control proves to be a disease-specific, reliable, and valid tool for revealing overall disease control from the patient's viewpoint. Both healthcare professionals and patients may find it to be a useful patient-reported outcome measurement for triaging IBD patients in China or complementing routine care.